Adaptive PID controller using for speed control of the BLDC motor - Mahmud, Md; Motakabber, S. M. A.; Alam, A. H. M. Zahirul; Nordin, Anis Nurashikin (IEEE, 2020)
Brushless DC Motor (BLDCM) is broadly utilized for some mechanical applications, given their high efficiency, high torque, and low volume. It is very hard to tune the parameters and accomplish full force highlights utilizing a basic custom PID controller. An adaptive PID controls can meet the highlights and are anything but difficult to enrol. The list items test that any adaptive PID controller has favoured both the PI controller and the customary Tahitian PID controller. This paper applies an Adaptive PID controller dependent on the extra blunder of a turn around control sign to comprehend non-linearity, parameter varieties, and burden travel issues that happen in the BLDC motor drive framework. The test results are exhibited to demonstrate that Adaptive PID controllers dependent on the extra mistake of the reverse control signal are fit for the following movement, just as diminishing the impact of parameter changes. The proposed adaptive PID controller model has done by MATLAB/SIMULINK.